Temporal variations in air pollution at two roundabouts in the city of Cotonou, Benin - Karine L.M. Codjo-Seignon; Vincentia M.C. Houssou; Philippe Kossolou; Ghislain E. Sopoh; Martin P. Aina (SAGE Publishing, 2021)
Background: Air pollution has caused health and environmental problems around the world. In this study we analysed the temporal evolution of air pollution in Cotonou regarding the standards of Benin and of World Health Organization (WHO). Methods: Solar-powered electrochemical sensors (CO: carbon monoxide, SO2: sulphur dioxide, and O3/NO2: ozone/nitrogen dioxide) and photoionization detectors (for NMVOC: nonmethane volatile organic compounds) were permanently installed and monitored from June 2019 to March 2020 at Akpakpa PK3 (A) and Vèdokô Cica-Toyota (B) roundabouts. Results: CO and SO2 concentrations at both roundabouts were significantly higher on weekends than on weekdays. The concentrations of NMVOC and O3 / NO2 on Sunday differed considerably from the other days of the week at A and B, respectively. There was a positive linear correlation between the concentrations of CO and SO2, O3 / NO2 and SO2, and CO O3 / NO2 to B, and only between CO and O3 / NO2, in A. At the two sites, the average of SO2 concentrations (in μg/m3) were higher than the WHO standard (500) for an exposure of 10 minutes (2258 A and 2143 B) and the Benin standard (1300) for 1 hour exposure (2181 in A and 2092 in B). Conclusion: Air pollution varies in hours and days in Cotonou. Standards are respected, except for SO2. Particular attention should be paid to the concentrations and the possible sources of gas. More sophisticated monitoring system should be put in place.